Impact of the creation of the Sports Secretary on the municipal sports development index and access to public sports facilities and equipment in the city of Recife (Research, Society and Development, 2024)
This study aimed to analyze and compare the impact of the establishment of the Secretariat of Sports over the course of the administration from 2021 to 2024, using the Cultural Development and Access Index (IDAC) as the primary evaluation indicator. The investigation employed a quantitative methodological design, divided into data collection from the administrations (from 2013 to 2020 and from 2021 to 2024), calculation of the absolute and relative IDAC of both, and statistical analysis for comparison. The data were subjected to a Kolmogorov-Smirnov normality test and Levene's test for homogeneity of variances. An independent t-test was used to compare the values. The analyses were conducted using JASP 16.2 software, adopting a significance level (p